Medical Mistrust and Its Impact Among People Experiencing Homelessness. - Brzoza, Vicki; Ryan, Elyse Mia (Clinical Journal of Oncology Nursing, 2025)
This article examines perspectives of people experiencing homelessness related to perceived challenges with obtaining breast cancer screenings, education, and health care, as well as how these perspectives contribute to medical mistrust. It also considers how social determinants intersect and intensify hardships faced by this population, potentially explaining negative perceptions of healthcare providers. The intersectionality within individuals and their identities, challenges, and community affiliations can exacerbate the impact of medical mistrust and related social constructs. These findings have important implications for oncology nursing practice, particularly in addressing structural barriers and fostering trust within this vulnerable community.